Dois ensaios sobre a desigualdade de oportunidades no Brasil - Adamczyk, Willian Boschetti (2017)
The present dissertation is composed by two essays on inequality of opportunities in Brazil. It is measured the inferior bound of income inequality and opportunities inequality in Brazil, bringing evidences to its ethical and unethical components. Applying the parametric methodology developed by Ferreira and Gignoux (2011) to PNAD data between 2001 and 2014, the Essay I shows the reduction in the inequality of opportunities index (IOp) from 0,106 to 0,066, a drop of 37,37% in the period. In comparison, inequality of income measured by the MLD index decreased significantly from 0,55 to 0,40, a drop of 27,2%. This fall in total inequality is composed in 53% by a decrease in the unfair share of inequality, meanwhile, the fair share is responsible for 47% of the reduction. The weight of circumstances in inequality of opportunities remains nearly constant, with 58% corresponding to the informality of workers, 27% for differences in color, and 14% for differences in sex. Comparing the income of the circumstances groups, is showed that the mean income of the most disadvantaged group, “nonwhite informal women”, consists only in 29,5% the mean income of the most advantaged group, “white formal men”. However, the most disadvantaged groups were the ones that gained more with the growth of income. Amongst the states, Santa Catarina offers the best index of inequality of opportunities, meanwhile Piauí sits at the least position. It is clear the relative disadvantage of states in North and Northeast regions, presenting systematically the larger indexes of inequality of opportunity. The Essay II studies the inequality of opportunity in the state of Rio Grande do Sul in the year of 2010 using the Municipal Inequality of Opportunity Index (IOp-M) constructed by Figueiredo et al. (2013). The spatial distribution of the results is analyzed and its relations with productive variables. The LISA analysis allows to verify the presence of spillovers of IOp-M from a city to its neighbors. The formation of spatial clusters shows that unfair inequalities suffer from spatial dependence. Considering solely the productive structure, Roemer’s (1998) Compensation Principle suggests that the allocative rule of public resources demands a redirection of resources to regions with higher IOp-M`s which are more dependent on public sector and agriculture, meanwhile municipalities with higher industry, commerce, and services participation have lower compensational needs.